2016
DOI: 10.4149/bll_2016_080
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of echocardiography and ECG in heart failure with preserved ejection fraction

Abstract: OBJECTIVE: The aim of this study was to evaluate characteristics of patients with heart failure (HF) with preserved ejection fraction (HFPEF) and to assess prognostic predictors in 2-year follow-up. METHODS: We included prospectively 109 patients admitted to the internal department for HF, grouped into HFPEF (EF>40 %, n = 63) and HF with reduced EF (HFREF) (EF ≤ 40 %, n = 46). Preserved right ventricular systolic function (PRV) was defi ned as the peak systolic tricuspid annular velocity (S') > 10.8 cm/s. RESU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…There is limited literature which has investigated the clinical relevance of ECG changes in HFpEF 21,22 . The study carried out by Cenkerova et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is limited literature which has investigated the clinical relevance of ECG changes in HFpEF 21,22 . The study carried out by Cenkerova et al .…”
Section: Resultsmentioning
confidence: 99%
“…There is limited literature which has investigated the clinical relevance of ECG changes in HFpEF 21,22 . The study carried out by Cenkerova et al demonstrated that HFpEF patients who died during the course of FU, had a tendency to have a prolonged QTc interval (427 ± 42 ms vs. 454 ± 42 ms, P = 0.058) 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The definition of HeFNEF varied among studies (Appendix II). In addition, different cutoffs for left ventricular ejection fraction (LVEF) were used to define HeFNEF: ≥40% (Cenkerova, Dubrava, Pokorna, Kaluzay, & Jurkovicova, ; Danciu et al, ; Hendry, Krisdinarti, & Erika, ), >40% (Hawkins et al, ; Olsson et al, ), ≥45% (Adabag et al, ; Donal et al, ; Joseph et al, ; Komajda et al, ; Nikolaidou et al, ; Shah et al, ), >45% (Ho et al, ; Lee et al, ; Park et al, ; Zile et al, ), ≥50% (Gigliotti et al, ; Gijsberts et al, ; Hummel, Skorcz, & Koelling, ; Khan et al, ; Lund et al, ; Martinez Santos et al, ; Masoudi et al, ; Menet et al, ; O'Neal et al, ; Pascual‐Figal et al, ; Peyster, Norman, & Domanski, ; Senni et al, ; Shenkman et al, ; Yap et al, ), >50% (Eicher et al, ; Oskouie, Prenner, Shah, & Sauer, ; Sanchis et al, ; Selvaraj et al, ; Shah et al, ), and ≥55% (Varadarajan & Pai, ). The following methods were used to measure ejection fraction: echocardiography, nuclear scintigraphy, and contrast ventriculography.…”
Section: Resultsmentioning
confidence: 99%
“…In the studies we identified, the prevalence of atrial fibrillation or atrial flutter on ECG was 12%–46% (Adabag et al, ; Cenkerova et al, ; Donal et al, ; Ho et al, ; Khan et al, ; Lee et al, ; Masoudi et al, ; Nikolaidou et al, ; Olsson et al, ; Oskouie et al, ; Pascual‐Figal et al, ; Peyster et al, ; Sanchis et al, ; Selvaraj et al, ; Senni et al, ; Shah et al, ; Yap et al, ). The percentage of patients with a history of atrial fibrillation (where reported) was greater (Lee et al, ; Shah et al, ).…”
Section: Resultsmentioning
confidence: 99%